2013
DOI: 10.1002/fuce.201200183
|View full text |Cite
|
Sign up to set email alerts
|

Durability and Performance of High Performance Infiltration Cathodes

Abstract: The performance and durability of solid oxide fuel cell (SOFC) cathodes consisting of a porous Ce0.9Gd0.1O1.95 (CGO) infiltrated with nitrates corresponding to the nominal compositions La0.6Sr0.4Co1.05O3–δ (LSC), LaCoO3–δ (LC), and Co3O4 are discussed. At 600 °C, the polarization resistance, Rp, varied as: LSC (0.062 Ω cm2) < LC (0.079 Ω cm2) < Co3O4 (0.27 Ω cm2). High temperature X‐ray diffraction revealed a number of different phases in LSC and LC. The electrochemical performance of the LSC‐infiltrated CGO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…[ 446 ] Recently, Samson et al directly infi ltrated Co 3 O 4 into a porous Ce 0.9 Gd 0.1 O 1.95 framework, and a surprisingly low ASR of 0.27 Ω cm 2 was obtained at 600 °C. [ 447,448 ] Under similar conditions, the ASRs of La 0.6 Sr 0.4 Co 1.05 O 3-δ and LaCoO 3-δ infi ltrated GDC electrolyte were 0.062 Ω cm 2 and 0.079 Ω cm 2 , respectively, which were just slightly better than that of the Co 3 O 4 infi ltrated GDC. The authors attributed the high performance of Co 3 O 4 infi ltrated electrode to the beneficial interplay between the GDC and Co 3 O 4 , which seemed to greatly enhance the surface exchange properties.…”
Section: Electrodes Infi Ltrated Into the Scaffold Of Electrolytesmentioning
confidence: 95%
See 2 more Smart Citations
“…[ 446 ] Recently, Samson et al directly infi ltrated Co 3 O 4 into a porous Ce 0.9 Gd 0.1 O 1.95 framework, and a surprisingly low ASR of 0.27 Ω cm 2 was obtained at 600 °C. [ 447,448 ] Under similar conditions, the ASRs of La 0.6 Sr 0.4 Co 1.05 O 3-δ and LaCoO 3-δ infi ltrated GDC electrolyte were 0.062 Ω cm 2 and 0.079 Ω cm 2 , respectively, which were just slightly better than that of the Co 3 O 4 infi ltrated GDC. The authors attributed the high performance of Co 3 O 4 infi ltrated electrode to the beneficial interplay between the GDC and Co 3 O 4 , which seemed to greatly enhance the surface exchange properties.…”
Section: Electrodes Infi Ltrated Into the Scaffold Of Electrolytesmentioning
confidence: 95%
“…[ 442 ] Some other alkaline earth metal element free oxide materials were also tried with infi ltration method to prepare high-performance oxygen reduction electrodes. [443][444][445][446][447][448] With high electrical conductivity (≈190 S cm −1 ) and compatible TEC (12.2 × 10 −6 K −1 ) but low oxygen ionic conductivity, [ 443 ] the spinel Cu 1.25 Mn 1.75 O 4 phase was impregnated into an YSZ framework to form a new composite cathode, [ 444 ] and an infi ltration amount of 50 wt% was found to exhibit the lowest polarization resistance of 0.3 Ω cm 2 at 750 °C, which was much lower than 8.5 Ω cm 2 from a LSM infi ltrated YSZ cathode. In addition, the charge transfer process was likely to be the rate determining step at above 750 °C.…”
Section: Electrodes Infi Ltrated Into the Scaffold Of Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the infiltration step, a material is added in the form of an aqueous precursor solution to an existing scaffold, where the desired material forms during subsequent conditioning of the electrode . An unintended consequence of this approach can be the formation of minor secondary phases, either from the infiltrate itself or from reactions between the infiltrate and the scaffold . Recent investigations on La 1− x Sr x CoO 3− δ (LSC)‐based electrodes have indicated that the presence of minor secondary phases may even improve electrode performance due to the formation of hetero‐interfaces .…”
Section: Introductionmentioning
confidence: 99%
“…An unintended consequence of this approach can be the formation of minor secondary phases, either from the infiltrate itself or from reactions between the infiltrate and the scaffold . Recent investigations on La 1− x Sr x CoO 3− δ (LSC)‐based electrodes have indicated that the presence of minor secondary phases may even improve electrode performance due to the formation of hetero‐interfaces . These and other studies of secondary phases often draw conclusions correlating electrode composition with performance based on ex situ studies and in operando electrochemical characterization.…”
Section: Introductionmentioning
confidence: 99%